The power of family? The change in academic achievement after breakdown of the biological family - Tamás Keller (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
There is fairly broad consensus among scholars that divorce damages pupils' academic achievement. However, further clarification is necessary concerning the role of pupil characteristics immediately prior to this unpleasant event, and the extent to which the changing circumstances are reflected in the decline in school achievement. In this regard, more insight is provided into the social-status gradient of the test-score gap. The empirical analysis is based on a unique Hungarian administrative educational panel dataset covering three entire school cohorts. The sample contains 88,000 pupils who experienced biological family breakdown between the 6th and the 8th grade. Classroom fixed-effect regressions reveal that it is largely derived characteristics that account for the drop in test scores, rather than the changing material environment. Ruling out individual and classroom-level differences in test scores, the remaining test-score gap between those from intact and broken biological families is interpreted as a sign of damaged emotional stability. Emotional factors are known to have an effect on pupils' academic achievement, but without some exogenous variance (like the breakdown of the biological family) it would be hard to demonstrate empirically its impact on academic achievement.
Keywords: I21; I24; J12; 330; Breakdown of biological family; Academic achievement; Emotional stability